Climate Change Adaptation and Mitigation using Information and Communication Technology - Ajwang, Stephen O.; Nambiro, Alice W. (International Journal of Computing Sciences Research; Vol 6 (2022): Vol 6, 2022)
Purpose- This study aims to determine how ICT can be used to address climate change by enhancing adaptation and mitigation measures. Methodology - The research looked at the existing literature on ICT use in climate change adaptation and mitigation. The findings of the literature review were divided into three categories: the role of ICT as an adaptive and mitigating factor, as well as a contributing factor to climate change; role of global ICT companies in combating climate change; and the course of action for increased adoption of ICT to fight climate change. Findings - According to the study, technological advances driven by cutting-edge innovation in ICT have been recognized as effective means of combating climate change by revealing signals of changing climate, analyzing and modeling climate change, and implementing mitigation and adaptation measures that improve human resilience. The study also found that, while ICT has been hailed as a game-changer in combating climate change and its variability, a few limitations remain, as ICT may contribute to some extent to the ongoing climate change. The study also discovered that major ICT companies such as Google, IBM, and Microsoft have increased their efforts to reduce greenhouse gas emissions. Conclusion - As an essential component of mitigating the effects of climate change, ICT provides new opportunities for knowledge discovery and real-time information exchange. The application of ICT in conjunction with appropriate laws and regulations has the potential to drive the fundamental transformation required in the global fight against climate change. Recommendation - The study recommends that Kenya and the rest of the world embrace and use ICT to mitigate and adapt to climate change to accelerate the achievement of SDGs and other national economic blueprints.